Imagination : a manifesto / Ruha Benjamin. - Benjamin, Ruha (Norton shorts., 2024)
Princeton professor Ruha Benjamin believes in the liberating power of the imagination. Deadly systems shaped by mass incarceration, ableism, digital surveillance and eugenics emerged from the human imagination but they have real-world impacts. To fight these systems and create a world that works for all of us, we will have to imagine things differently. As Benjamin shows, educators, artists, technologists and more are experimenting with new ways of thinking and tackling seemingly intractable problems. Drawing from the work of these visionaries, this volume explores the possibility and practices required to imagine and create more just and habitable worlds.